Design Unmanned Aerial Vehicle Integrated Camera Near Infra-red to Observe the Plant Health - Rizki Wahyu Pratama; Ferry Hadary; Redi Ratiandi Yacoub (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Plant health is an essential factor to reducethe number of import in a country. In this research, we usepaddy as an example to understand plant health. Ourresearch is motivated by our belief that technology mightaid in reducing chances of failed paddy harvest inIndonesia. To understand the plant health of paddy, wedesigned unmanned aerial vehicle (UAV) integrated pocketcameras to record near infra-red (NIR) light. Apart fromNIR light data, we obtained the normalized differencevegetation index (NDVI) values of paddy to observe theplant health based on the photosystem metabolism thatabsorb red light and blue light and reflects green l ight andNIR light. Based on the test results, the values of NDVI aregiven -0.819672, 0.395018, 0.346667, 0.032680, 0.705628 and0.302817. Based on values of NDVI, we conduct avalidation test with farmers to compare NDVI values wi thactual conditions on the ground. Based on the test, theobtained value of NDVI was in accordance with the actualconditions in the field.